2019
DOI: 10.1074/jbc.ra119.011602
|View full text |Cite
|
Sign up to set email alerts
|

In vitro trackable assembly of RNA-specific nucleocapsids of the respiratory syncytial virus

Abstract: The templates for transcription and replication by respiratory syncytial virus (RSV) polymerase are helical nucleocapsids (NCs), formed by viral RNAs that are encapsidated by the nucleoprotein (N). Proper NC assembly is vital for RSV polymerase to engage the RNA template for RNA synthesis. Previous studies of NCs or nucleocapsid-like particles (NCLPs) from RSV and other nonsegmented negative-sense RNA viruses have provided insights into the overall NC architecture. However, in these studies, the RNAs were eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Indeed, it is now admitted that oligomerization of N proteins is closely related or coupled to their ability to interact with RNA ( 29 ). Recent biochemical studies on the capacity of recombinant RSV and MeV monomeric N to interact with RNA and oligomerize revealed that, whereas MeV monomeric N can form in vitro nucleocapsids in the presence of RNA of 6 nucleotides in length ( 56 ), the RSV monomeric N assembles only into rings under the same conditions ( 57 ). Altogether, these results suggest that, more than a direct role of RNA in IB assembly, the oligomerization of N seems crucial for the scaffold involved in the formation of IBs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is now admitted that oligomerization of N proteins is closely related or coupled to their ability to interact with RNA ( 29 ). Recent biochemical studies on the capacity of recombinant RSV and MeV monomeric N to interact with RNA and oligomerize revealed that, whereas MeV monomeric N can form in vitro nucleocapsids in the presence of RNA of 6 nucleotides in length ( 56 ), the RSV monomeric N assembles only into rings under the same conditions ( 57 ). Altogether, these results suggest that, more than a direct role of RNA in IB assembly, the oligomerization of N seems crucial for the scaffold involved in the formation of IBs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the 56 nt-long HeV leader sequence, which is transcribed and separated from the mRNA transcripts during the RdRp transcription mode, falls within the occupancy range for a single tetradecameric ring (84 nt). This purine-rich sequence is also likely preferentially encapsidated over RNA chains with an even purine-pyrimidine ratio [49][50][51]. The HeV trailer sequence is shorter than the leader and similarly rich in purine bases.…”
Section: Discussionmentioning
confidence: 99%
“…While N-RNA interactions are thought to be sequence non-specific and HeV N model building was done in a sequence-agnostic manner, some evidence for MeV suggests RNA encapsidation exhibits a preference for purine-rich sequences and importantly, the antigenomic leader sequence [49]. Similar preferences for purine rich and leader-specific RNA were also observed for the more distantly related RSV and VSV, respectively [50,51]. Indeed, the HeV genomic and antigenomic leader sequences are purine rich as well, with ∼70% and ∼63% purines for the genomic and antigenomic leaders, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a fraction of these RNAs are nuclease resistant, indicating that they can be encapsidated 40 . Although it is well accepted that N-RNA rings would be expected to contain 70 nt of RNA encapsidated by 10 N protomers 6,7 , it has been shown that if purified recombinant N protein is incubated with RNAs as short as 14 nt, it can form N-RNA rings that are of similar dimensions as those reconstituted with longer RNAs 41 . This suggests either that RNA is only required to nucleate the encapsidation event and that subsequent N-N interactions allow formation of a 10-protomer ring that is not necessarily entirely RNA-bound, and/or that short N-RNA complexes can associate together to form 10 N-protomer rings containing multiple small RNA oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%